COMPARISON OF EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF TEAM GAMES AND TOURNAMENT (TGT) TYPE AND JIGSAW TYPE IN MATHEMATICS LEARNING OF GRADE VII AT PUBLIC JUNIOR HIGH SCHOOLS IN CENTRAL MALUKU DISTRICT - Wabula, Zainuddin (Sains Global Institut, 2019)
The study aims at comparing the effectiviness between cooperative learning model of Jigsaw type and cooperative learning model of Teams Games Tournament (TGT) type on quadrangle material. The comparison of the effectiveness is based on (1). Learning outcomes, (2) students? activities, and (3) students? response. The type of the study is quasi experiment research. The populations were all of the students of grade VII at public junior high schools in Central Maluku district. Samples consisted of two classes, namely the experiment group I taught by using cooperative learningmodel of Jigsaw type and the experiment group II taught by using TGT type, which were obtained by employing simple random sampling technique. The instruments used were RPP, THB, LOAS, questionnaire of students? response, observation sheet of learning implementation, and LKS. Data collection consisted of learning outcomes, data of students? activities in learning, and data of students? response on tools and learning. Data of students? activities and sudents?response were analyzed by using the mean scores; whereas, data of learning outcomes was analyzed by using descriptive analysis and inferential analysis. The results of the study reveal that the implemantation of cooperative learning model of Jigsaw type was in very effective category with learning outcomes was in high category, the mean score 87,83, median 88, maximum 100, minimum 67, and standard of deviation was 7,58. The result of hypothesis test at the level of significance =0,05 with t test indicate thet the learning using cooperative learning model of Jigsaw type is effective than cooperative learning model of TGT type on quadrangle material in grade VII at public junior high school in Central Maluku district.